LOPAKHIN’S CAPITALIST POINTS OF VIEW DEALING WITH SOCIAL CLASS AND CLASS STRUGGLE IN ANTON CHEKHOV’S THE CHERRY ORCHARD - Andy Dwi Cahya Putra; Eko Budi Setiawan; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2017)
The research entitled Lopakhin’s Capitalist Points of View Dealing with Social Class and Class Struggle in Anton Chekhov’s The Cherry Orchard aims to find out Lopakhin’s capitalist points of view dealing with social class and class struggle in Anton Chekhov’s The Cherry Orchard. This research focuses on the drama entitled The Cherry Orchard as primary data. The writer uses several theories in this research; they are theory of marxism, capitalism, social class, and class struggle. Moreover, library research is used as a method of collecting the data. In addition, descriptive research is applied in order to understand and learn the conditions, habits, opinions of some characters in Anton Chekhov’s The Cherry Orchard. Furthermore, the sociological approach is used to explain Lopakhin’s capitalist points of view presented in The Cherry Orchard. Key Words: Capitalism, Social Class, Class Struggle.